Cases on teacher preparation in deaf education - Neild, Nena Raschelle; Graham, Patrick Joseph (Advances in higher education and professional development (AHEPD), 2023)
"The intent of this publication is to support instruction in a variety of deaf education courses providing sample cases and examples for the students to work through and discuss. The case studies will encourage critical thinking and thoughtful reflection related to a variety of deaf education environments and situations"--